2021
DOI: 10.1016/j.csbj.2021.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in functional annotation and prediction of the epitranscriptome

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 191 publications
(241 reference statements)
1
6
0
Order By: Relevance
“…M7G modification is one of the most common base modification methods in gene regulation and plays an important role in maintaining the structural stability of RNA, affecting RNA processing and metabolism, and regulating protein translation. [7,8] Studies have shown that N7-methylguanosine modification-related lncRNAs (m7G-lncRNAs) participate in the regulation of the molecular biological processes of tumor cells in vivo and affect the occurrence and development of tumors. [9] However, to the best of our knowledge, no studies of m7G-lncRNAs in THCA have been reported.…”
Section: The Authors Have No Funding and Conflicts Of Interest To Dis...mentioning
confidence: 99%
See 1 more Smart Citation
“…M7G modification is one of the most common base modification methods in gene regulation and plays an important role in maintaining the structural stability of RNA, affecting RNA processing and metabolism, and regulating protein translation. [7,8] Studies have shown that N7-methylguanosine modification-related lncRNAs (m7G-lncRNAs) participate in the regulation of the molecular biological processes of tumor cells in vivo and affect the occurrence and development of tumors. [9] However, to the best of our knowledge, no studies of m7G-lncRNAs in THCA have been reported.…”
Section: The Authors Have No Funding and Conflicts Of Interest To Dis...mentioning
confidence: 99%
“…M7G modification is one of the most common base modification methods in gene regulation and plays an important role in maintaining the structural stability of RNA, affecting RNA processing and metabolism, and regulating protein translation. [ 7 , 8 ]…”
Section: Introductionmentioning
confidence: 99%
“…Then, DNA fragments assembled with adapters were amplified to prepare DNA clusters, and the clusters were sequenced (Gao et al, 2020;Zhang et al, 2021). The sequences obtained using fastq software (Version 0.20.0) were filtered by removing reads that contained adapters and poly-N as well as those with a lower sequencing quality (<Q 20).…”
Section: Comparative Genomic Analysismentioning
confidence: 99%
“…According to extant literature findings ( 10 ), tRNA guanine N7 methyltransferase, which belongs to the S-adenosylmethionine (SAM)-dependent RNA methyltransferase family, catalyzes m7G modification. In addition, m7G is also involved in many RNA metabolic processes in the human body, including transcription, mRNA splicing, and translation ( 11 ).…”
Section: Introductionmentioning
confidence: 99%